Single Capsule Bismuth Quadruple Therapy for Eradication of H. pylori Infection: A Real-Life Study - Gravina, Antonietta G.; Priadko, Kateryna; Granata, Lucia; Facchiano, Angela; Scidà, Giuseppe; Cerbone, Rosa; Ciamarra, Paola; Romano, Marco (Frontiers in Pharmacology, 2021)
Background and aim Bismuth quadruple therapy (BQT) or non-bismuth quadruple therapy (i.e. concomitant therapy) (CT), are the first-line regimens to eradicate H. pylori infection in areas with high prevalence of clarithromycin (CLA) resistance. Guidelines suggest that in areas of high prevalence of H. pylori strains with double resistance (i.e. CLA + metronidazole), BQT should be preferred to CT. The aim of this study was to evaluate the efficacy and safety of BQT administered through the 3-in-one pill (Pylera) formulation in a large series of H. pylori-infected patients, naive to treatment in a region with high CLA and dual resistance. Patients and methods We treated 250 patients (148F and 102 M, mean age 48.6 years) with H.pylori infection naïve to treatment. Patients received esomeprazole 40 mg bid and Pylera 3 tablets qid for 10 days. Diagnosis of H. pylori infection was through 13C Urea Breath Test (13C UBT), or Stool Antigen Test (SAT) or histology, as appropriate. Evaluation of eradication was through 13CUBT at least 45 days after end of therapy. Incidence of treatment-related adverse events (TRAEs) was assessed through a questionnaire at the end of treatment. Compliance was considered good if at least 90% of medication had been taken. Statistical analysis was per Intention-to-treat (ITT) e Per Protocol (PP). 95% confidence intervals (CI) were calculated. Results 1) 13 patients (5.2%) discontinued therapy due to side effects; 2) Eradication rates in ITT and PP were 227/250 (90.8%; 95% CI 86.3%-93.7%) and 226/237 (95.3%; 95% CI 91%-99%) respectively; 3) The prevalence of TRAEs was 26.8%; 5) Adherence to treatment was good with compliance greater than 90%. Conclusions In this real life study we demonstrate that in an area with a high prevalence of H. pylori strains with CLA or CLA + metronidazole resistance , BQT using Pylera is an effective therapeutic strategy with ITT eradication rates higher than 90%; 2) This therapy is associated with good compliance and low incidence of side effects.